2007
DOI: 10.1590/s1806-37132007000400014
|View full text |Cite
|
Sign up to set email alerts
|

Um estudo retrospectivo dos aspectos epidemiológicos da tuberculose na comunidade do Complexo de Manguinhos localizado em área urbana do Rio de Janeiro, Brasil, 2000-2002

Abstract: Para descrever alguns aspectos da tuberculose em favelas, foi realizado um estudo retrospectivo no Complexo de Manguinhos, Rio de Janeiro (RJ) Brasil. Em um total de 290 casos notificados entre 2000 e 2002, 75,8% eram casos novos. A taxa de incidência foi de 157, 205 e 145/100.000, respectivamente. Embora tenha sido observada tendência de diminuição dos números de casos no período de estudo, esta não foi significante, sugerindo manutenção da endemia. Portanto, embora exista um serviço de saúde no local, estrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
0
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
2
1
0
4
Order By: Relevance
“…The predominance of the disease in males and adults is consistent with the literature,( 24 , 25 ) as is the lower level of education( 26 ) and the predominance of cases among Mulattos and Blacks. ( 27 ) In addition, alcohol consumption was very common among patients with tuberculosis, which is similar to results reported by other authors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The predominance of the disease in males and adults is consistent with the literature,( 24 , 25 ) as is the lower level of education( 26 ) and the predominance of cases among Mulattos and Blacks. ( 27 ) In addition, alcohol consumption was very common among patients with tuberculosis, which is similar to results reported by other authors.…”
Section: Discussionsupporting
confidence: 90%
“…O predomínio da doença no sexo masculino e entre adultos é consistente com a literatura,( 24 , 25 ) assim como a menor escolaridade( 26 ) e a predominância de casos entre pardos e pretos. ( 27 ) Também similar a resultados de outros autores,( 28 , 29 ) o uso de álcool foi muito frequente entre os pacientes com tuberculose.…”
Section: Discussionunclassified
“…Among the patients with resistant strains, none was HIV positive; the same was reported by a study conducted in Rio de Janeiro, Brazil 14 . Another study, also conducted in Rio de Janeiro, found no significant association between TB/HIV co-infection and resistance 15 .…”
Section: Discussionsupporting
confidence: 76%
“…Recently, the number of new cases in Brazil has declined significantly, from 51.44/100,000 in 1999 to 37.12/100,000 in 2008 (7). Nonetheless, in 2008, incidence in the Rio de Janeiro municipal area was 68.64/100,000 (8), the highest in the country, while in some of the municipality's most underserved areas, such as the Manguinhos district, annual incidence reached 145/100,000 (9). …”
Section: Introductionmentioning
confidence: 99%